COMMUNICATION STRATEGY OF CORRECTIONAL GUARDIANS IN SHAPING THE SELF-CONCEPT OF CHILD PRISONERS AT LPKA CLASS I TANGERANG - Mukhtar, Dimas; Muhammad, Ali (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The purpose of this study was to determine the communication strategy of correctional guardians in shaping the self-concept of child prisoners and to find out the factors that cause negative self-concept in child prisoners while undergoing coaching at the Tangerang Class I Child Special Development Institution. This research uses qualitative research methods with a phenomenological approach. This study concludes that the correctional guardian, in developing a communication strategy, uses the stages of knowing the audience, compiling messages, determining methods, and using media. However, in its implementation, improvement efforts are needed so that the formation of a positive self-concept in child prisoners becomes more optimal. The factors that form the negative self-concept of child prisoners while undergoing coaching are social stigma, lack of closeness with parents, lack of access to psychological support, and not forming warm and personal communication and connections with correctional guardians. It is recommended that the Special Development Institute for Children Class I, Tangerang, in this case, can carry out special training for correctional guardians in communicating effectively with child prisoners. Keywords : Communication Strategy; Self-Concept; Child Prisoners; Correctional Guardians